Children's schooling and parental migration: Empirical evidence on the 'left behind' generation in Albania - Gianna Claudia Giannelli; Lucia Mangiavacchi (Institute for the Study of Labor (IZA), 2010)
This article investigates the long-term effects of parental migration abroad on the schooling of children left behind in Albania. Although parents' migration usually benefits children economically, the lack of parental care may cause relational and psychological problems that may affect children's welfare in the long-term. The phenomenon of children left behind -mainly by fathers - is very relevant in Albania where migration has represented the only viable way to cope with increasing poverty and the absence of public resources for sustaining households' incomes. Between 1990 and 2005 in Albania 21.7% of children under 18 have been left behind, with an average parental absence of 9.5 months. Using detailed information on family migration drawn from the Living Standard Measurement Survey for 2005, multiple choice models are applied to evaluate the school progression of older children and adolescents. A duration analysis of school participation with both discrete and continuous time models is then performed. The results show that past parental migration has a negative effect on school attendance in the long-term with higher hazards of school drop-outs for children left behind. These results are robust to the use of different econometric techniques and model specifications.
Keywords: J13; J18; O15; P36; 330; Children; schooling; migration; duration analysis; Albania; Kinder; Bildungsniveau; Familiensoziologie; Alleinerziehende; Eltern; Auswanderung; Statistische Bestandsanalyse; Albanien